Subclinical bovine mastitis and environmental risk factors in small producers of dairy cattle raised in the high altitude - Sánchez Herencia, Diana (2022)
The aim of this study was to estimate the prevalence of subclinical mastitis and identify environmental risk factors in dairy cattle from small producers in the high Peruvian mountains. A cross-sectional study was carried out, analyzing milk samples per mammary quarter from 300 Brown Swss cows belonging to 38 producers from the district of Santa Rosa, Melgar, in Puno, Peru. The area is located at an altitude of 3900-4300 m. The California Mastitis Test (CMT) was used for the detection of subclinical mastitis, while the identification of environmental factors was done through surveys and inspections to the sites. The prevalence of subclinical mastitis was 47.0% (141/300) and 21.2% (254/1200) at the level of cows and mammary quarters, respectively, without significant differences between quarters (p>0.05). The 15.75 and 24.25% of the four mammary quarters were positive to the degree of traces and level 1 of the CMT, respectively. Within the environmental factors, the type of milking (p=0.0004), the let-down of the milk by the calf (p=0.0001) and two milkings per day (p=0.001) were determining factors for the presentation of subclinical mastitis, while the pre-milking hygiene of the cow and the hygiene of the milkers did not denote importance.